Síntese e propriedades ópticas de sistemas coloidais contendo nanopartículas de ouro dispersas em óleo de mamona - Silva, Eid Cavalcante da (2008)
This dissertation of master s degree presents the results and discussions related to the synthesis, characterization, and stability of a new colloidal system containing gold nanoparticles (AuNP) dispersed in castor oil. In parallel, the stability of the system against agglomeration, after addition of other organic solvents in the medium was evaluated. In collaboration with the Laboratory of Optics and Materials of the Institute of Physics of the Federal University of Alagoas, the non linear optical properties of the new colloidal system were evaluated. The colloids were synthesized via wet chemistry, using a two-phase method, which consists of a mixture of an aqueous solution of HAuCl4, castor oil, ethanol, and an aqueous solution of KOH. Several colloid syntheses had been carried out, using ratios of Au/OH⎯/castor oil, in order to establish the convenient concentration ratio of the components to lead the formation of relative stable colloids. The AuNPs had been characterized by Transmission Electronic Microscopy (TEM), ultraviolet-visible spectroscopy (UV-Vis), and the quantification of gold content in the colloid was done by Inductively Coupled Plasma-Atomic Emission Spectrometry (ICP-AES). The new colloidal system of nanoparticles of gold dispersed in castor oil presented interesting non linear optical properties. These properties had been evaluated via z-scan technique